Bimineralic Middle Triassic ooids from Hydra Island: Diagenetic pathways and implications for ancient seawater geochemistry. (15th August 2020) - Varkouhi, Shahab; Jaques Ribeiro, Luis Miguel
Abstract: This study reports on the occurrence of formerly bimineralic, ancient, calcitic coated grains, including half‐moon ooids and micritic to microsparitic ooids in the Middle Anisian (Middle Triassic) grain flow from Hydra Island (Greece), and discusses their importance for palaeoseawater geochemical interpretations. The bi‐partite fabric in half‐moon ooids resulted from early pre‐compaction rapid dissolution of both aragonitic cortices and the more‐soluble components of the high‐Mg calcite core in the primary ooid, as well as the collapse of less‐dissolved remnants to the bottom of the oomouldic cavity which was later filled with calcite cement. Zonal, micritic to microsparitic ooids formed through intracortical dissolution of primary aragonite lamellae which were later replaced by (micro)sparry calcite. At the same time, recrystallization of original high‐Mg calcite layers to micrite occurred. The stratigraphic occurrence of the investigated bimineralic ooids conforms to the global distribution of carbonate ooids through the Middle Triassic period. The cementation history of the grain flow hosting coated grains is well documented by the paragenetic sequence established in half‐moon ooids which predicts that calcite precipitated under burial (shallow to deep) conditions. The main control on precipitation of bimineralic ooids was the Mg/Ca ratio of seawater, with lesser influences from seawater temperature, salinity and ρCO2 which promoted the degree of carbonate saturation, leading to higher precipitation rates for both aragonite and high‐Mg calcite. The studied bimineralic ooids represent a change in the global carbonate factory during the Middle Triassic in response to secular variations in the chemistry of palaeoseawater. Abstract : This study reports the occurrence of formerly bimineralic, ancient, calcitic coated grains, including half‐moon ooids and micritic to microsparitic ooids in the Middle Anisian (Middle Triassic) grain flow from Hydra Island (Greece), and their importance for palaeoseawater geochemical interpretations. The studied bimineralic ooids represent a change in the global carbonate factory during the Middle Triassic in response to secular variations in the chemistry of palaeoseawater.